Staffing in the Lebanese American University Library - Khreidieh, Said I. (1996)
This work has surveyed staffing procedures at the Lebanese American University Library LAUL (Beirut campus), comparing these with authoritative concepts of human resource management. The research methods were based on statistical data provided by LAUL and on interviews conducted with library staff from all the staffing levels. The main difficulties encountered by the library were found to be related to space, insufficient staff, poor communication and training, lack of motivation and an excessive number of student assistants. Practical and realistic solutions are recommended for these problems.